Evaluation of metal oxide nanoparticles for adsorption of gas phase ammonia. Issue 1 (February 2017) - Rezaei, Ebrahim; Schlageter, Beauregard; Nemati, Mehdi; Predicala, Bernardo
Abstract: MgO, ZnO, CuO, and TiO2 nanoparticles along with activated charcoal (AC) were evaluated for ammonia adsorption. Adsorption experiments were conducted under atmospheric pressure in a packed bed column. Among the tested adsorbents, TiO2 had the highest equilibrium adsorption capacity of 6.87 mg NH3 g −1 followed by AC, ZnO, MgO, and CuO. Increasing gas flowrate negatively impacted TiO2 breakthrough adsorption capacity by lowering residence time of ammonia in the bed. Using Wheeler-Jonas expression, total mass transfer coefficient for ammonia adsorption on TiO2 was estimated as 1061 min −1 . Adsorption isotherms for 50 to 500 ppmv ammonia at temperatures in the range of 5–280 °C revealed that TiO2 equilibrium adsorption capacity decreased as temperature increased. Among the evaluated isotherms Langmuir-Freundlich best described the equilibrium adsorption data. Examination of exposed TiO2 by CNHS, TGA, and FT-IR revealed that molecular ammonia was the most abundant surface feature at room temperature, while for temperatures in the range of 70–280 °C formation of amido (NH2 ) and imido (NH) species through hydrogen abstraction from ammonia was evident. Using the characterization data a mechanism scheme for adsorption of ammonia on TiO2 nanoparticles was proposed.